The influence of consequence value and text difficulty on affect, attention, and learning while reading instructional texts. (December 2015) - Mills, Caitlin; D'Mello, Sidney K.; Kopp, Kristopher
Abstract: The present study investigated how consequence value influences affect, attention, and learning while reading instructional texts, and if text difficulty moderates these effects. Participants studied four instructional texts on research methods in a 2 × 2 consequence value (high vs. low) × text difficulty (easy vs. difficult) within-subjects experiment. Consequence value was manipulated by assigning two of the four texts as having high value and the other two as having low value with respect to a performance goal on a subsequent test, while text difficulty was manipulated via experimenter-created easy and difficult versions of the texts. We hypothesized that consequence value would induce mild anxiety, which would focus attention and facilitate learning, and that text difficulty would moderate the influence of consequence value. Partially consistent with the predictions, high consequence value led to lower valence, higher arousal, longer reading times, and positively predicted knowledge transfer. Arousal mediated the relationship between consequence value and knowledge transfer, but only when the texts were difficult, thereby suggesting moderated mediation. Highlights: Participants studied four instructional texts on research methods. Consequence value and text difficulty were manipulated in a 2 × 2 design. Consequence value had direct effects on affect, reading time and knowledge transfer. Arousal mediated the relationship between consequence value and knowledge transfer. Text difficulty moderated the mediation through arousal.